2019
DOI: 10.1186/s13568-019-0916-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiviral activity of Bacillus licheniformis-fermented products against porcine epidemic diarrhea virus

Abstract: Bacillus licheniformis (B. licheniformis) is commonly used as probiotic and its secondary metabolites are attractive anti-microbial candidate. In the present study, we aimed to evaluate the antiviral activity of crude extracts from B. licheniformis against porcine epidemic diarrhea virus (PEDV), a highly contagious enveloped porcine virus that has caused great economic loss in pigs. In vivo, PEDV-infected piglets supplemented with air-dried solid state fermentative cultivate containing B. licheniformis-ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…L. platarum , normal flora in porcine gastrointestinal tracts, has been reported to induce endogenous antimicrobial peptide synthesis in weaning piglets and improve pig growth and pork quality 12 , 13 . Pigs that received a probiotic-containing Bacillus licheniformis were shown to reduce porcine epidemic diarrhea virus infected vero cells 14 . In addition, a probiotic‐containing Bacillus licheniformis and Bacillus subtilis spores could improve productive performance and carcass quality in pigs 15 .…”
Section: Introductionmentioning
confidence: 99%
“…L. platarum , normal flora in porcine gastrointestinal tracts, has been reported to induce endogenous antimicrobial peptide synthesis in weaning piglets and improve pig growth and pork quality 12 , 13 . Pigs that received a probiotic-containing Bacillus licheniformis were shown to reduce porcine epidemic diarrhea virus infected vero cells 14 . In addition, a probiotic‐containing Bacillus licheniformis and Bacillus subtilis spores could improve productive performance and carcass quality in pigs 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent data shows a decrease in death rates with daily intake of these products ( Bayindir and Bayindir, 2020 ). Besides, several bioactive peptides, isolated and identified from fermented soy products, have been reported to exhibit antiviral activities against HIV, HSV, influenza virus, and human respiratory illness virus ( Yamai et al, 2003 ; Wei et al, 2015 ; Peng et al, 2019 ). Some of these peptides have also been evaluated as effective immunomodulators ( Yimit et al, 2012 ; Kiewiet et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al ( 2014 ) stated an AMP from B. subtilis , P34 for inhibiting canine adenovirus type 2 (CAV-2), canine coronavirus (CCoV), canine distemper virus (CDV), canine parvovirus type 2 (CPV-2) and equine arteritis virus (EAV). Starosila et al ( 2017 ) and Peng et al ( 2019 ) reported AVPs for porcine epidemic diarrhea virus. Kassaa et al ( 2014 ) described the effect of LAB probiotics against viral infections.…”
Section: Discussionmentioning
confidence: 99%